(3GdXhGgQ GdfbOjI Ydj GdeSJhi GdOhdjs - (3edGc(B, (3hSGes; (3edGc hSGes ((3HjQhJs (3OGQ Gdefgd GddHfGfj ddWHGYI h GdfTQs, 2001)
(3jCJj gPG GdcJGH aj SdSdI JYGdL GdbVGjG GdfbOjI hGdeGdjI (B.(3Jdc GdSdSdI JTJed Ydi eDda KGdK SjUOQ dGMbG , hjNUU dOQGSI GdHhQUGJ hGdCShGb GdeGdjI GdYGdejI (B.(3hYdi ZQGQ GdeDda GdChd (B" (3GdfbhO hGdSjGSGJ GdOGNdjI (B" (3abO UjZ gPG GdeDda HCSdhH eHSW eY GdMQU GdTOjO Ydj eQGYGI GdObI GdYdejI , heG GdGeJdI GdeJYOOI ,GdJj COQLJ , EdG HZjI age CYeb ddehVhYGJ GdeWQhMI(B. (3CSS Jchjf ejRGf GdeOahYGJ hGdbjhO GdJj jJWdHgG ,BdjGJ EYGOI GdJhGRf Edj ejRGf GdeOahYGJ ,GdJhGRf aj GdGbJUGO GdeaJhM Ydj GdNGQL hYdGbI ejRGf GdeOahYGJ HCge GdeJZjQGJ GdGbJUGOjI , Shb GdUQa ,GdJSYjQI , GdYGedhf aj GdShb hESJQGJjLjI eUOQj GdChGeQ , GOhGJ GdUQa GdeTJbI hGdCShGb GdefXeI ddYbhO ddCLd hdNjGQGJ GdUQa ,GfXeI GdUQa GdeQJHWI HJONd GdSdWGJ GdfbOjI aj Shb GdUQa , GdJhGRf Ydj GdUYjO GdGbJUGOj Gdcdj haYGdjI (BPax (3GdSjGSJjf GdfbOjI hGdehGRfjI aj Xd fXGej GdUQa GdJGHJ hGdYGFe , bGYOI GdUQa (B- (3GdOgH hYUQ Gd (Bamericana (3GdJNdj Yf GdUQa GdKGHJ hGdGfJbGd Gdj JLQHI GdYhe ZjQ GdJGe MJj GdYGe (B1978 (3, GdYhe ZjQ GdJGe dCSYGQ GdUQa efO GdYGe (B1979 (3GdOhdGQ cfbO Ohdj hCOGI JhXja OhdjIs
Keywords: (3GdGbJUGO GdOhdjs